Persepsi Masyarakat Terhadap Pengelolaan Wisata Pantai Minanga Desa Kotajin Utara Kecamatan Atinggola Kabupaten Gorontalo Utara - Nur Fadhilah Ahmad; Sri Nuryatin Hamzah; Sitti Nursinar (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The Minanga Beach area is a new tourist destination, which is currently visited by many tourists. As an initial step in developing coastal tourism objects, it is necessary to know the public's perception of the existence of these attractions, for sustainable tourism. This research aimed to determine the type of tourism management in Minanga beach and the perception of the community towards the management of Minanga Beach, Kotajin Utara Village, Atinggola District, Gorontalo Utara Regency. The respondent determination method used purposive sampling. The number of respondents determined was 100 respondents distributed in four hamlets in Kotajin Utara Village. The number of respondents in this research was determined using the Slovin formula. Data were analyzed using quantitative analysis supported by qualitative analysis. The results showed that the management of Minanga Beach tourism is a co-management which is collaborative management between the government and the community. Community perception of Minanga Beach tourism management is in good criteria with an average of 365 or about 73%.